Structure induced wide range wettability: Controlled surface of micro-nano/nano structured copper films for enhanced interface. (10th September 2021) - Cao, Lili; Luo, Bingwei; Gao, Hongli; Miao, Min; Wang, Tao; Deng, Yuan
Graphical abstract: Highlights: Cu films with controllable micro-nano/nano surface is obtained. The wide range wettability is realized by controlled surface structure. A wide range of contact angles ranging from 6° to 152° are fabricated. Cluster-nanoparticle structure possesses a superhydrophobic surface. Structure-induced wettability is important to tune and simplify the interface. Abstract: The wettability of materials used in the production of devices employed in various technological domains have attracted significant attentions. Therefore, it is important to design the surfaces of these materials such that they can provide the required surface free energy and simplify the interfacial structure. Herein, various Cu films with a highly controllable surface wettability and a wide range of contact angles ranging from 6° to 152° were fabricated, and the corresponding mechanism was discussed. A wide range of wettability was realized by controlling the surface structure of the Cu film. The nanogap structure of the vertical nanowire-array film led to a high surface free energy. Similarly, the oblique nanowire-array film increased the surface free energy; however, the surface free energy was dependent on the size of the nanowires rather than on the nanogaps owing to the crystallinity of the film. Additionally, cluster-nanowire-array films were designed to realize a wettability transition from hydrophilicity to hydrophobicity with a constant surface free energy. The Cu foam possessed a superhydrophilic surface owing to its high porosity, whereas the cluster-nanoparticle structure possessed a superhydrophobic surface. In addition, we noted that the structure-induced wettability played an important role in tuning the semiconductor and metal interfacial stress and simplifying the interfacial structure. Furthermore, the outstanding electrical conductivity of the Cu films indicates its promising potential as an electrode. The structure-induced wettability proposed in this study can be applied for a wide range of materials, particularly for films used for advanced applications.